1995
DOI: 10.1074/jbc.270.9.4412
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin Stimulates Two Signal Transduction Pathways, cAMP Accumulation and Ca2+ Mobilization, in Bovine Aortic Endothelial Cells

Abstract: The biological action of adrenomedullin, a novel hypotensive peptide, on bovine aortic endothelial cells, was examined. The specific binding of adrenomedullin to these cells was observed, and adrenomedullin was found to induce intracellular cAMP accumulation in a dose-dependent manner. EC50 for the cAMP accumulation was about 100 times lower than the apparent IC50 for the binding assay. Adrenomedullin also induced increase of intracellular free Ca2+ in endothelial cells in a dose-dependent manner. The Ca2+ res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
211
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 345 publications
(221 citation statements)
references
References 31 publications
8
211
1
1
Order By: Relevance
“…It must be mentioned however, in contradiction to the theory that ADM inhibits aldosterone secretion, that ADM itself stimulates two signal transduction pathways; cAMP accumulation and Ca 2+ mobilisation (Shimekake et al 1995). Both these second messenger mechanisms are utilised by various factors, such as ACTH, to stimulate aldosterone secretion.…”
Section: Discussionmentioning
confidence: 76%
“…It must be mentioned however, in contradiction to the theory that ADM inhibits aldosterone secretion, that ADM itself stimulates two signal transduction pathways; cAMP accumulation and Ca 2+ mobilisation (Shimekake et al 1995). Both these second messenger mechanisms are utilised by various factors, such as ACTH, to stimulate aldosterone secretion.…”
Section: Discussionmentioning
confidence: 76%
“…[2][3][4] AM not only induces vasorelaxation but also regulates growth and death of these vascular cells. [5][6][7][8][9][10] These findings suggest that AM plays an important role in maintaining vascular homeostasis in an autocrine and/or paracrine manner.…”
mentioning
confidence: 77%
“…Consistent with this, in cultured vascular endothelial cells, AM was found to stimulate phospholipase C activation and inositol 1,4,5-triphosphate formation, resulting in an elevation of the intracellular Ca 2ϩ level and activation of NO synthase. 65 Kato et al reported that AM inhibited serum deprivation-induced apoptosis of cultured rat vascular endothelial cells. 61 Blockade of the endogenous AM by anti-AM anti-serum impaired the inhibitory effect of the nonimmune serum on apoptosis, suggesting an autocrine or paracrine role for AM.…”
Section: Vascular Protective Effects In Vitromentioning
confidence: 99%